IT Sophistication: Implementation on State Owned Banks in Indonesia - Sambas Ade Kesuma; Siti Zabedah Saidin; Aidi Ahmi (International Review of Management and Marketing, 2016)
The objective of this paper is to determine the IT Sophistication (technological, informational, functional, and managerial sophistication) implementation among the Indonesian state owned bank. The result of this survey shows that shows a relatively high level on the implementation of IT sophistication on state owned banks in Indonesia. The result of this study shows a high level of technological sophistication among the Indonesian state owned banks. The majority of state owned banks have adopted high technologies, high level of informational sophistication, high participation on information system development (functional sophistication), and high plan on information system development (managerial sophistication) on state owned banks in Indonesia. The result of this study would contribute to the development of IS research, particularly to extend the use of comprehensive dimension of IT sophistication dimension in banking sector and provide information that would help the managements of state owned banks to improve the implementation of IT.